THE DIRECTION OF CHANGE IN SUSTAINABILITY REPORTING DISCLOSURES ON EXTENSIVE AND MORE STANDARDIZED REPORTING - Nurhayati, Lina; Irfan, Andi (LPPM Universitas Malikussaleh, 2024)
In the direction of changes in extensive and standardized sustainability reporting, companies are expected to establish disciplined and credible sustainability reporting and disclosure programs using recognized frameworks such as the Global Reporting Initiative (GRI), Sustainability Accounting Standard Board (SASB), CDP, or DJSI. The future of sustainability reporting will involve transparent, clear and detailed reporting on sustainability issues, with a focus on strategy, implementation and performance measurement. The movement towards broader and more standardized sustainability reporting is driven by the need for transparent and meaningful ESG (Environment, Social and Governance) disclosures that drive value for stakeholders and public companies. The research method used in this study is literature examination, which involves collecting literature relevant to the topic, selecting the most related literature, organizing the literature based on topics, concepts, or themes, critical analysis and evaluation, and compiling the results by showing relationships and patterns. emerge from every literature. The results of this study can be used to assist companies in developing effective and credible sustainability reporting and disclosure programs.